Determining the sites of neural adaptations to resistance training: A systematic review and meta-analysis - Siddique, U.; Rahman, S.; Frazer, A. K.; Pearce, A. J.; Howatson, G.; Kidgell, D. J. (Sports Medicine, 2020)
Background: Resistance-training causes changes in the central nervous system (CNS); however, the sites of these adaptations remain unclear. Objective: To determine sites of neural adaptation to resistance-training by conducting a systematic review and meta-analysis on the cortical and subcortical responses to resistance-training. Methods: Evidence from randomized controlled trials (RCTs) that focused on neural adaptations to resistance-training was pooled to assess effect estimates for changes in strength, cortical, and subcortical adaptations. Results: The magnitude of strength gain in 30 RCTs (n = 623) reported a standardised mean difference (SMD) of 0.67 (95% CI 0.41, 0.94; P < 0.001) that measured at least one cortical/subcortical neural adaptation which included: motor-evoked potentials (MEP; 19 studies); silent period (SP; 7 studies); short-interval intracortical inhibition (SICI; 7 studies); cervicomedullary evoked potentials (CMEP; 1 study); transcranial magnetic stimulation voluntary activation (VATMS; 2 studies); H-reflex (10 studies); and V-wave amplitudes (5 studies). The MEP amplitude during voluntary contraction was greater following resistance-training (SMD 0.55; 95% CI 0.27, 0.84; P < 0.001, n = 271), but remained unchanged during rest (SMD 0.49; 95% CI -0.68, 1.66; P = 0.41, n = 114). Both SP (SMD 0.65; 95% CI 0.29, 1.01; P < 0.001, n = 184) and active SICI (SMD 0.68; 95% CI 0.14, 1.23; P = 0.01, n = 102) decreased, but resting SICI remained unchanged (SMD 0.26; 95% CI - 0.29, 0.81; P = 0.35, n = 52). Resistance-training improved neural drive as measured by V-wave amplitude (SMD 0.62; 95% CI 0.14, 1.10; P = 0.01, n = 101), but H-reflex at rest (SMD 0.16; 95% CI - 0.36, 0.68; P = 0.56; n = 57), during contraction (SMD 0.15; 95% CI - 0.18, 0.48; P = 0.38, n = 142) and VATMS (MD 1.41; 95% CI - 4.37, 7.20; P = 0.63, n = 44) remained unchanged. Conclusion: There are subtle neural adaptations following resistance-training involving both cortical and subcortical adaptations that act to increase motoneurone activation and likely contribute to the training-related increase in muscle strength.